7.2k views
1 vote
Please answer this question​

Please answer this question​-example-1

2 Answers

1 vote

Simplify the integrand:


(\left(x-x^3\right)^(\frac13))/(x^4) = \frac{\left(x^3 \left(\frac1{x^2}-1\right)\right)^(\frac13)}{x^4}= \frac{x \left(\frac1{x^2} - 1\right)^(\frac13)}{x^4} = \frac{\left(\frac1{x^2}-1\right)^(\frac13)}{x^3}

Substitute y = 1/x² - 1 and dy = -2/x³ dx :


\displaystyle \int \frac{\left(\frac1{x^2}-1\right)^(\frac13)}{x^3} \, dx = -\frac12 \int y^(\frac13) \, dy \\\\ = -\frac12 * \frac34 y^(\frac43) + C \\\\ = \boxed{-\frac38 \left(\frac1{x^2}-1\right)^(\frac43) + C}

User Mukesh Yadav
by
4.8k points
5 votes


\rm \int \frac{(x - {x}^3 {)}^{ (1)/(3) } }{ {x}^(4) } dx \\

can be written as:-


\rm\int{(- (x^(3))/(3) + (x)/(3))/(x^(4)) d x} \\


\rm = {\int{(1 - x^(2))/(3 x^(3)) d x}} \\


\rm = {\left(\frac{\displaystyle \rm\int{(1 - x^(2))/(x^(3)) d x}}{3}\right)} \\


= \rm \frac{{\displaystyle \rm\int{\left(- (1)/(x) + (1)/(x^(3))\right)d x}}}{3} \\


= \rm \frac{{\left( \displaystyle \rm\int{(1)/(x^(3)) d x} - \int{(1)/(x) d x}\right)}}{3} \\


\rm \red{- \frac{\int{(1)/(x) d x}}{3} + \frac{\color{red}{\int{(1)/(x^(3)) d x}}}{3}=- \frac{\int{(1)/(x) d x}}{3} + \frac{\color{red}{\int{x^(-3) d x}}}{3}=- \frac{\int{(1)/(x) d x}}{3} + \frac{\color{red}{(x^(-3 + 1))/(-3 + 1)}}{3}=- \frac{\int{(1)/(x) d x}}{3} + \frac{\color{red}{\left(- (x^(-2))/(2)\right)}}{3}=- \frac{\int{(1)/(x) d x}}{3} + \frac{\color{red}{\left(- (1)/(2 x^(2))\right)}}{3}} \\


\rm\int{(- (x^(3))/(3) + (x)/(3))/(x^(4)) d x} = - \frac{\ln{\left(\left|{x}\right| \right)}}{3} - (1)/(6 x^(2))+C \\

User ParDroid
by
4.7k points